2021
DOI: 10.1111/cas.15217
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunodiagnosis panel for hepatocellular carcinoma based on bioinformatics and the autoantibody‐antigen system

Abstract: Hepatocellular carcinoma (HCC) is a malignancy with a dismal survival rate. The novel autoantibodies panel may provide new insights for the diagnosis of HCC. Biomarkers screened by two methods (bioinformatics and the antigen‐antibody system) were taken as candidate tumor‐associated antigens (TAAs). Enzyme‐linked immunosorbent assay was used to detect the corresponding autoantibodies in 888 samples of verification and validation cohorts. The verification cohort was used to verify the autoantibodies. Samples in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Studies have suggested that the combination of multiple anti-TAA autoantibodies as a panel could enhance the detection of cancer [ 20 , 44 , 45 ]. This study combined three anti-TAA autoantibodies as a panel; the panel could identify 68.0% HCC from NC with an accuracy of 88.2%, which was higher than those in any single one of the three autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that the combination of multiple anti-TAA autoantibodies as a panel could enhance the detection of cancer [ 20 , 44 , 45 ]. This study combined three anti-TAA autoantibodies as a panel; the panel could identify 68.0% HCC from NC with an accuracy of 88.2%, which was higher than those in any single one of the three autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a cumulative effect of (epi-) genomics and oncogenic networks/mechanisms might be contributing to this. Recently, a novel immunodiagnostic assay was developed to screen tumor-associated antigens (TAAs) associated with HCC, that includes RGS20 in a panel of eleven TAAs (AAGAB, C17orf75, CDC37L1, DUSP6, EID3, PDIA2, RGS20, PCNA, TAF7L, TBC1D13, and ZIC2) [ 38 ]. Thus, providing further evidence to support our study indicating the distinctive involvement of RGS20 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…DNAJC13 plays a role in vesicle formation and trafficking. Associations between increased levels of DUSP6 and HCC or liver cirrhosis have been reported ( Wu et al, 2022 ). S1PR2 inhibition mitigated liver fibrosis development and S1PR2 blockage has been shown to accelerate HCC progression in mice ( Yoshida et al, 2020 ; Kawai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%